2008
DOI: 10.1139/w08-056
|View full text |Cite
|
Sign up to set email alerts
|

B subunit ofEscherichia coliheat-labile enterotoxin as adjuvant of humoral immune response in recombinant BCG vaccination

Abstract: The B subunit of Escherichia coli heat-labile enterotoxin (LTB), a nontoxic molecule with potent biological properties, is a powerful mucosal and parenteral adjuvant that induces a strong immune response against co-administered or coupled antigens. In this paper, the effect of LTB on the humoral immune response to recombinant BCG (rBCG) vaccination was evaluated. Isogenic mice were immunized with rBCG expressing the R1 repeat region of the P97 adhesin of Mycoplasma hyopneumoniae alone (rBCG/R1) or fused to LTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
4
9
0
Order By: Relevance
“…As is the case with CT-B, the LT-B subunit is a less potent adjuvant than the LT holotoxin, but in many instances it has been shown to potentiate the response after mucosal immunization against inactivated virus, viral glycoproteins, and bacterial proteins; LT-B is also known to be an effective carrier in fusion proteins (Clements, 1990;Sanchez et al, 1986;O'dowd et al, 1999;Da Silva Ramos Rocha et al, 2008;Fingerut et al, 2005).…”
Section: E Coli Heat-labile Toxinmentioning
confidence: 99%
“…As is the case with CT-B, the LT-B subunit is a less potent adjuvant than the LT holotoxin, but in many instances it has been shown to potentiate the response after mucosal immunization against inactivated virus, viral glycoproteins, and bacterial proteins; LT-B is also known to be an effective carrier in fusion proteins (Clements, 1990;Sanchez et al, 1986;O'dowd et al, 1999;Da Silva Ramos Rocha et al, 2008;Fingerut et al, 2005).…”
Section: E Coli Heat-labile Toxinmentioning
confidence: 99%
“…The B subunit of Escherichia coli heat-labile enterotoxin (LTB) is highly immunogenic upon systemic (6,9,15) and mucosal (14,37) immunizations. Its adjuvant activity has been demonstrated with unrelated antigens, both coadministered (14,15) and linked by chemical conjugation or genetic fusion (6,14,37), exhibiting no toxic effect (8).…”
mentioning
confidence: 99%
“…The CT from Vibrio cholerae and LT from enterotoxigenic strains of E.coli are potent mucosal adjuvants. It has been found that CT induces a Th2 response (26), whereas LT induces a Th1‐biased immune response (27, 28). The B subunits of these toxins are less potent than the active toxins.…”
Section: Discussionmentioning
confidence: 99%